Health status, health-related quality of life, and socioeconomic outcome in childhood brain tumor survivors: a German cohort study. Issue 8 (22nd February 2019) - Scholtes, Cathy; Baust, Katja; Weinhold, Leonie; Creutzig, Ursula; Gnekow, Astrid; Hinz, Andreas; Kaatsch, Peter; Kreitz, Kiana; Langer, Thorsten; Rutkowski, Stefan; Singer, Susanne; Spix, Claudia; et al.
Abstract: Background: With rising numbers of childhood cancer survivors, somatic and socioeconomic outcome as well as health-related quality of life (QoL) gain increasing relevance. Based on the first nationwide German Survey on Life Situation, State of Health, and Quality of Life of Childhood Cancer Survivors, the VIVE survey, we report the outcome of survivors of childhood brain tumors localized in the posterior fossa. Methods: Two hundred seventy participants with a median follow-up period of 21.9 years completed a questionnaire on socioeconomic and somatic late effects as well as a standardized QoL questionnaire (European Organisation for Research and Treatment of Cancer QLQ-C30). Comparisons were performed between World Health Organization (WHO) grades I–II, WHO grades III–IV brain tumor survivors (BTS), and the general population adjusting for potential confounders. Results: The socioeconomic and QoL results of WHO grades I–II BTS were largely comparable to the general population, while grades III–IV BTS were at higher risk for significantly worse outcomes. Of WHO grades III–IV BTS, 36.8% were still living with their parents or in assisted living facilities compared with 16.1% of grades I–II BTS and 7.8% of the age-adjusted general population. Of grades III–IV BTS, 60.8% achieved at least an intermediate school degree in comparison to 80.5% of grades I–II BTS and 75.6% of the general population. Grades III–IV BTS developed up to 2 times more somatic late effects than survivors of grades I–II tumors. Conclusion: Derived from a large and homogeneous cohort, these results stress the importance of an appropriate follow-up period focusing not only on physical aspects but encompassing the entire living situation to allow patient-tailored support.